2014
DOI: 10.1002/rcs.1595
|View full text |Cite
|
Sign up to set email alerts
|

Robotic giant hiatal hernia repair: 3 year prospective evaluation and review of the literature

Abstract: Robotic approaches can minimize surgical trauma in patients with giant hiatal hernias and result in favourable outcomes in terms of anatomical recurrence and quality of life. With the availability of the da Vinci System, all patients with giant hiatal hernias can be offered a minimally invasive surgical option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
0
17
0
4
Order By: Relevance
“…In a 3-year prospective assessment, Morelli et al (2015) [27] analyzed six patients with giant hiatal hernias who underwent robotic repair using the da Vinci Surgical System. The average operating time was 182 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…In a 3-year prospective assessment, Morelli et al (2015) [27] analyzed six patients with giant hiatal hernias who underwent robotic repair using the da Vinci Surgical System. The average operating time was 182 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Among these papers were 10 literature reviews [9,[32][33][34][35][36][37][38][39][40], complemented with a meta-analysis in four [33,34,38,40]. These reviews described up to five randomized controlled trials [10,[41][42][43][44], 17 cohorts, case-control studies, or caseseries [11,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. One paper described pilot data to a later published RCT [61], two were case-reports [62,63].…”
Section: Robot-assisted Antireflux Surgery; Review Of Literaturementioning
confidence: 99%
“…Among these papers were 10 literature reviews , complemented with a meta‐analysis in four . These reviews described up to five randomized controlled trials , 17 cohorts, case‐control studies, or case‐series . One paper described pilot data to a later published RCT , two were case‐reports .…”
Section: Robot‐assisted Antireflux Surgery; Review Of Literaturementioning
confidence: 99%
“…1 While conventional laparoscopic repair for giant hiatal hernias is considered difficult, robotic technology is likely to result in an improved postoperative course. 2 Morelli et al 3 in their prospective study of 3 years with robotic da Vinci system included 6 patients for giant hiatal hernia repair, they showed that robotic approach in hiatal hernia repair can minimize the surgical trauma and lead to less anatomical recurrence and better quality of life.…”
Section: Introduction/backgroundmentioning
confidence: 98%